Study of Various Organic Mulch Sheet Compositions Usage towards The Growth and Yield of Cauliflower (Brassica oleracea Var Botrytis, L.) - Aniek, Aniek; Hasanah, Aniek; ., Hartawati (International Journal of Engineering and Technology, 2019)
The production decrease and the imported commodity increase were due to the low quantity and quality of cauliflower, it was also caused by pre-harvest factors including cultivation technique that mostly used non-biodegradable plastic mulch. Functionally, the seasonal organic mulch was less effective and thus it needed engineering technology in the form of organic mulch sheet. The selection of organic materials (water hyacinth, banana pseudostem and tannery waste) which were used as mulches have met the eco-friendly concept. This research was aimed to study the effect of various organic mulch sheet compositions usage towards the growth and yield of cauliflower. The result showed that the use of organic mulch sheet was significant compared to the treatment without using mulch with the yield increase by 72.18%. However, the results were not significantly different in various compositions and black silver plastic mulch (BSPM) treatments with the growth and yield as the observable variables. The temperature of  organic sheet mulch was between 25.10C – 29.10C; the soil temperature was between 25.9oC – 34.6oC; the soil humidity was between 66.1 - 78.2. The intensity of the light received was between 47,844.3 – 52,735 lux, meanwhile the light reflected was between 7,196.79 – 8,451.18 lux.